Indonesia's Social Enterprise: Policy Challenges and Support Needs - Sebastian Billy Anggara; Irma Tsuraya Choirinnida (Economics and Business Journal (ECBIS), 2025)
This research investigates the policy landscape surrounding social entrepreneurship in Indonesia, encompassing legal and regulatory frameworks, government initiatives, and institutional support for social enterprises. The study is crucial as it addresses an understudied area, aiming to inform policymakers, foster collaboration, stimulate economic development, and promote sustainable growth. The methodology involved qualitative interviews with eight social entrepreneurs across Indonesia. Collected data was analyzed using content analysis techniques, facilitated by the MAXQDA platform. Findings indicate that despite social entrepreneurship being an emerging field in Indonesia, there is a notable lack of effective policies and regulations. Six of eight respondents perceived inadequate current regulatory support, and half cited financial challenges as a significant issue. Conversely, seven respondents acknowledged existing government assistance, suggesting a willingness to support the sector. Based on these results, key recommendations for the government to foster a supportive ecosystem include developing non-overlapping policies, implementing substantive policy changes, promoting useful policies, simplifying bureaucracy, and engaging in direct dialogue with social entrepreneurs. The research concludes that addressing these areas can empower social entrepreneurs to create lasting social impact. This study uniquely fills a gap by directly engaging social entrepreneurs, though future research should include government representatives for broader perspectives.